Edukasi Self Care Pasca Vaksinasi Pada Kelompok Lansia Di Taba Penanjung Bengkulu Tengah - Encik Putri Ema Kemala; Tuti Anggriani Utama; Desi Susilawati (Jurnal Pengabdian Kepada Masyarakat, 2021)
AbstractThe government's policy of carrying out the Covid-19 vaccination in January 2021 is still getting doubts in the hearts of the people. The level of acceptance varies in each province, this is motivated by knowledge, personal experience, culture, religious beliefs, community attitudes. The problem with Taba teret sub-district partners is that 80% of vaccinations have not been achieved and many people do not want to take vaccinations at the puskesmas or other health facilities, this is due to concerns and lack of public knowledge about self-care after the covid-19 vaccination. Based on this phenomenon, we from the community service team of the D3 Nursing Study Program, Faculty of Mathematics and Natural Sciences, Bengkulu University, took part in educating the public about post-vaccination self-efficacy in the Elderly Group in Taba Penanjung Bengkulu. The community service method uses a mentoring and socialization approach by means of lectures, questions and answers, discussions which are attended by 12 people. The results of this community assessment for the level of public knowledge before and after education in the category were obtained from 12 participants, 67% answered incorrectly on the question "Corona vaccine is only able to prevent severe COVID-19 symptoms". After the education there were 100% of the participants answered correctly on the questions. The increase difference is 60% increase. It is necessary to carry out continuous education and examine factors that influence vaccination acceptance in the elderly. Keywords: acceptance, educasion, covid-19,self care,  vaccination AbstrakKebijakan pemerintah dengan melaksanakan vaksinasi Covid-19 pada bulan Januari 2021  hingga saat ini,  masih mendapatkan keraguan di hati masyarakat. Tingkat penerimaan berbeda-beda di setiap provinsi, hal ini dilatar belakangi oleh pengetahuan, pengalaman pribadi, kebudayaan, keyakinan agama, sikap masyarakat. Permasalahan mitra kecamatan Taba teret adalah belum tercapainya vaksinasi 80% serta banyak masyarakat yang belum mau mengikuti vaksinasi di puskesmas atau fasilitas kesehatan lainnya, hal ini dikarenakan kekhawatiran dan kurangnya pengetahuan masyarakat tentang perawatan diri pasca vaksinasi covid-19. Berdasarkan fenomena tersebut kami dari tim pengabdian masyarakat prodi D3 Keperawatan FMIPA Universitas Bengkulu ikut handil dalam mengedukasi masyarakat tentang self efikasi Pasca Vaksinasi Pada Kelompok Lansia Di Taba Penanjung Bengkulu. Metode pengabmas menggunakan pendekatan pendampingan dan sosialisasi dengan cara ceramah, tanya jawab, diskusi yang diikuti 12 orang. Hasil pengkajian masyarakat ini untuk tingkat pengetahuan masyarakat sebelum dan sesudah edukasi dalam kategori didapatkan dari 12 peserta terdapat 67% menjawab salah pada pertanyaan “Vaksin corona hanya mampu mencegah gejala COVID-19 berat”. Setelah edukasi terdapat 100% peserta menjawab dengan benar pada pertanyaan. Selisih peningkatan adalah 60% meningkat. Perlunya dilakukan edukasi berkesinambungan dan mengkaji faktor yang mempengaruhi penerimaan vaksinasi pada lansia. Kata kunci : covid-19, edukasi, self care, vaksinasi